2004
DOI: 10.1007/s00114-004-0526-8
|View full text |Cite
|
Sign up to set email alerts
|

Clocks for sex: loss of circadian rhythms in ants after mating?

Abstract: This paper describes experiments on the locomotor activity rhythm of queens of the ant species Camponotus compressus, which were performed to investigate the consequences of mating on circadian clocks. Locomotor activity rhythm of virgin and mated queens was monitored individually under constant conditions of the laboratory. The locomotor activity rhythm of virgin queens entrained to a 24 h (12:12 h) laboratory light/dark (LD) cycle and free-ran under constant dim red light (RR) with a free-running period ( ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Previous reports claim that, in sharp contrast to the virgin queens, the mated queens do not show any rhythmicity of activity (McCluskey 1992). In one of our previous experiments we had reported that during such arrhythmicity the mated queens laid eggs, and displayed robust circadian rhythmicity in some other phenomena such as brood care, and the circadian rhythm of locomotor activity reappeared as soon as the egg-laying phase was over (Sharma et al 2004b). It appears that the apparent loss of circadian rhythms might not be due to arrhythmic circadian clocks, but due to loss of coupling between activity and the circadian clocks (Sharma et al 2004b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports claim that, in sharp contrast to the virgin queens, the mated queens do not show any rhythmicity of activity (McCluskey 1992). In one of our previous experiments we had reported that during such arrhythmicity the mated queens laid eggs, and displayed robust circadian rhythmicity in some other phenomena such as brood care, and the circadian rhythm of locomotor activity reappeared as soon as the egg-laying phase was over (Sharma et al 2004b). It appears that the apparent loss of circadian rhythms might not be due to arrhythmic circadian clocks, but due to loss of coupling between activity and the circadian clocks (Sharma et al 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…The periodicity of the locomotor activity rhythm was estimated by subjecting the primary data to Fourier spectral analysis (Sharma et al 2004b). The t of the locomotor activity rhythm in the two steady states of the media workers was subjected to mixed-model analysis of variance (ANOVA).…”
Section: Methodsmentioning
confidence: 99%
“…Shortly after mating, however, they become unattractive to males, shed their wings, and try to hide. Their activity cycles and phototactic behavior change substantially (Sharma et al, 2004;Lone et al, 2012). This is accompanied by immediate alterations of their cuticular profiles, which might make them unattractive to males (Oppelt and Heinze, 2009) or modify the physico-chemical properties of cuticular waxes to adjust to a life in a more humid place in the ground (Johnson and Gibbs, 2004;Hora et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Egg-laying queens of ants [49,50] and honeybees [51,52] are active around the clock with no circadian rhythms. This pattern of activity may be related to the remarkable fecundity of these queens, which are typically not engaged in brood care.…”
Section: (D) Activity Around the Clock Associated With Reproductive Omentioning
confidence: 99%